The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s40534-014-0057-8
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive neuro-fuzzy interface system for gap acceptance behavior of right-turning vehicles at partially controlled T-intersections

Abstract: Gap acceptance theory is broadly used for evaluating unsignalized intersections in developed countries. Intersections with no specific priority to any movement, known as uncontrolled intersections, are common in India. Limited priority is observed at a few intersections, where priorities are perceived by drivers based on geometry, traffic volume, and speed on the approaches of intersection. Analyzing such intersections is complex because the overall traffic behavior is the result of drivers, vehicles, and traf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…However, these studies are focused on modeling driver's behaviour. Recently, works are also reported on modeling gap acceptance behaviour of right turning vehicles at partially controlled three-legged intersections using adaptive neuro-fuzzy interface system and found that the predictions for major right turning ranged from 75% to 82% whereas for minor right turning, it is 87% to 89% (Sangole and Patil, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, these studies are focused on modeling driver's behaviour. Recently, works are also reported on modeling gap acceptance behaviour of right turning vehicles at partially controlled three-legged intersections using adaptive neuro-fuzzy interface system and found that the predictions for major right turning ranged from 75% to 82% whereas for minor right turning, it is 87% to 89% (Sangole and Patil, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the fuzzy logic system is more complex; thus, it is difficult for the human brain to understand the causality existing in such system [25]. According to recent literature [26], an adaptive neuro-fuzzy inference system (ANFIS) is a combination of neural network and fuzzy logic approaches; hence, it inherently has the advantages of both, such as having a good…”
Section: Establishing the Real-time Crash Risk Prediction Modelmentioning
confidence: 99%
“…To obtain the more accurate real-time crash risk prediction model, we used the main factors influencing the crash risk as the input variables (as shown in Table 1) and the crash risk as the output variable to train ANFIS of real-time crash risk in this study. All the input variables were fuzzy variables, which should be described and measured using linguistic rather than precise numerical values [26]. In this study, each input variable was divided into the following linguistic variables: negative big (NB), negative small (NS), zero (ZO), positive small (PS), and positive big (PB).…”
Section: Layer 2 Fuzzification Layermentioning
confidence: 99%
“…Thus, describing the risk perception of drivers using one particular formula is difficult. According to recent literature [8], an adaptive neuro-fuzzy inference system (ANFIS) is a combination of neural network and fuzzy logic approaches; hence, it inherently has the advantages of both, such as having a good learning mechanism and reasoning capability. Accordingly, we adopted ANFIS to model drivers' risk perception at unsignalized intersections in China in this study.…”
Section: Quantifying Risk Perception Of Driversmentioning
confidence: 99%